Boxing fatalities in relation to rule changes in Japan: secondary data analysis. Issue 3 (3rd July 2018) - Teramoto, Masaru; Cross, Chad L.; Cushman, Daniel M.; Willick, Stuart E.
ABSTRACT: Objectives : To examine whether changing weigh-in from the same day of the match to the day before the match and prohibiting 6-oz gloves are associated with fatalities in boxing matches sanctioned by the Japan Boxing Commission (JBC). Methods : We analyzed the rates of boxing fatalities before and after the two rule changes above via secondary analysis of data. Demographics and boxing records of deceased boxers were examined using descriptive statistics, exact binomial test the Mann-Whitney-Wilcoxon test and Fisher's exact tests. Results : As of this study, a total of 38 boxers (23.9 ± 3.3 years of age) reportedly died due to injuries sustained in JBC-sanctioned boxing matches since 1952. Changing weigh-in to the day before the match or prohibiting 6-oz gloves was not significantly associated with the rates of boxing fatalities 5 years and 10 years before and after the rule changes ( p  > 0.05). Deceased boxers after these rule changes were significantly older, completed significantly more rounds in the final match, and were significantly less likely to lose the previous match (prior to the final match) and to do so by knockouts ( p  < 0.05). Conclusion : Changing weigh-in to the day before the match and prohibiting 6-oz gloves may not result in reducing boxing fatalities.